Detection of the eaeA gene in Escherichia coli from chickens by polymerase chain reaction - Kilic, Ayse; Ertas, Hasan Basri; Muz, Adile; Ozbey, Goekben; Kalender, Hakan (Tubitak Scientific & Technological Research Council Turkey, 2007)
The aim of this study was to isolate Escherichia coli from chickens and to determine the presence of the eaeA gene, a virulence factor detected in E. coli, in the isolates by polymerase chain reaction (PCR). Different chicken organs were inoculated onto blood agar and biochemical tests were performed on the suspicious isolates. E. coli was isolated from 48% (48/100) of the samples. DNA was extracted from these isolates and was amplified by PCR, using a pair of primers derived from the eaeA (virulence) gene. In the agarose gel examination of PCR products, 48% (48/100) of the isolates were determined to have this virulence factor.
Keywords: Eschenchia coli; PCR; chicken; eaeA gene